Singapore's Insider Trading Prohibition and its Application to Take-over Transactions - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2007)
Provides an overview of insider trading regulation in Singapore, noting the government's policy objective to promote market fairness. Outlines the scope of prohibited conduct, exceptions, defences and penalties, and compares Singapore's regime with insider trading regulation in other jurisdictions. Considers in particular the application of the legislation to takeovers. Suggests that the offence is drafted too widely and could have a detrimental effect on investor confidence and Singapore's status as a key financial centre.